Regulacja ekonomiczna jako teoria grup interesu - Borkowska, Bożena (The economic regulation as a theory of interest groups, 2005)
Beginning with G. Stigler (1971) and continuing with S. Peltzman (1976) and G. Becker (1983, 1985), the Chicago School has challenged the public interest theory by offering economic theories of regulation often called economic theories of interest groups. The mains theses and implications of these theories are discussed in this article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 131-140